Nonlinear Vibrations Excited by Limited Power Sources - Balthazar, Jose Manoel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book covers a wide range of applied engineering research compactly presented in one volume, and shows innovative practical engineering solutions for automotive, marine and aviation industries, as well as power generation related to nonlinear vibrations excited by limited power sources. While targeting primarily the audience of professional scientists and engineers, the book can also be useful for graduate students, and for all of those who are relatively new to the area and are looking for a single source with a good overview of the state-of-the-art as well as up-to-date information on theories, analytical, numerical methods, and their applications in design, simulations, testing, and manufacturing. The readers will find here a rich mixture of approaches, software tools and case studies used to investigate and optimize diverse powertrains, their functional units and separate machine parts based on different physical phenomena, their mathematical model representations, solution algorithms, and experimental validation.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Machinery; Energy harvesting; Control engineering; Robotics; Automation; Multibody Systems and Mechanical Vibrations; Machinery and Machine Elements; Energy Harvesting; Control, Robotics, Automation; Vibration; Nonlinear mechanics